Modification of Superabsorbent Hydrogels for Industrial Wastewater Treatment - Md. Owaleur Rahman; Md. Abdul Halim; Anjan Deb; Shafi Ahmed; Md. Wasikur Rahman; N. C. Dafader; S. M. Nur Alam; Shahjalal Khandaker; Md. Jahangir Alam (Advances in Polymer Technology)
A breakthrough in superabsorbent hydrogel (SAH) preparation was studied in the current issue by blending potato starch and acrylic acid for wastewater treatment. Gamma irradiation source (60Co irradiation) was used to irradiate SAH from 1 to 10 kGy dose at room temperature (~27°C). The swelling ratio, water absorption, equilibrium water content, and gel fraction properties of the hydrogel were investigated. The as-prepared hydrogel treated with KOH (THG) showed excellent absorption capacity but less mechanical stability compared to untreated hydrogel (UHG). The gel fraction of treated SAH was slightly lower in methanol, but the utmost in water at 5 kGy infers the proper grafting of SAH at this point. The prepared SAH was characterized using scanning electron microscopy (SEM) and Fourier transform infrared (FTIR) to investigate the surface morphology and molecular interaction, respectively. Moreover, this study’s focal point is to propose an alternative method to remove chromium and methylene blue by SAH from industrial wastewater. The Cr adsorption capacity of UHG was higher than that of THG because the proton’s replacement is easier than that of K by Cr. On the other hand, THG was found to be more efficient in removing methylene blue from industrial wastewater due to the presence of an easily ionized group (–COOK) in SAH. Therefore, the hydrogel can be proposed as a potential superabsorbent to remove heavy metals and organic dyes from industrial wastewater.